2020
DOI: 10.1117/1.jbo.25.11.112907
|View full text |Cite
|
Sign up to set email alerts
|

Rapid tissue oxygenation mapping from snapshot structured-light images with adversarial deep learning

Abstract: Significance: Spatial frequency-domain imaging (SFDI) is a powerful technique for mapping tissue oxygen saturation over a wide field of view. However, current SFDI methods either require a sequence of several images with different illumination patterns or, in the case of singlesnapshot optical properties (SSOP), introduce artifacts and sacrifice accuracy. Aim: We introduce OxyGAN, a data-driven, content-aware method to estimate tissue oxygenation directly from single structured-light images. Approach: OxyGAN i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…The principle of the technique is based on diffusion theory, introducing a spatially modulated source into the steady-state diffusion equation and realizing spatial resolution measurements. In the past 10 years, SFDI has been mainly used in medical and biomedical fields, such as skin disease detection [12,13], blood oxygen content detection [14,15], pig skin burn level detection [16], etc. In recent years, SFDI has been applied to agricultural product quality detection, such as apple bruise detection [17] and pear bruise detection [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The principle of the technique is based on diffusion theory, introducing a spatially modulated source into the steady-state diffusion equation and realizing spatial resolution measurements. In the past 10 years, SFDI has been mainly used in medical and biomedical fields, such as skin disease detection [12,13], blood oxygen content detection [14,15], pig skin burn level detection [16], etc. In recent years, SFDI has been applied to agricultural product quality detection, such as apple bruise detection [17] and pear bruise detection [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile a comparison with the state-of-the-art techniques in Table 3 showed superiority in the performance of our diagnostic method. Unlike the study in [23], our technique is unaffected to ambient light with the use of the high power laser source. In addition, SFDI is reported in [23] to suffer from limited imaging depth and require rigid control of technique.…”
Section: Discussionmentioning
confidence: 99%
“…But variability in the quality of the image captured using the CytoCam incident dark field imaging camera system and the background noises were reported as the potential confounding factors precluding clinical evaluation. Two other works in this direction is by Mason et al [23] and Ossama et al [24]. The authors in [23] suggested the use of generative adversarial network (GAN) to estimate both uncorrected and profile-corrected tissues oxygenation, and showed an accuracy of 96.5 %.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical properties can also be estimated more quickly using a lighter‐weight twin U‐Net architecture with a GPU‐optimized look‐up table [103]. Further, chromophores can be computed in real‐time with reduced error compared with an intermediate optical property inference by directly computing concentrations from structured illumination at multiple wavelengths using conditional GANs [155].…”
Section: Applications In Biomedical Opticsmentioning
confidence: 99%